2014
DOI: 10.1248/bpb.b13-00233
|View full text |Cite
|
Sign up to set email alerts
|

<i>ent</i>-Kaurane and <i>ent</i>-Pimarane Diterpenes from <i>Siegesbeckia pubescens</i> Inhibit Lipopolysaccharide-Induced Nitric Oxide Production in BV2 Microglia

Abstract: The extract of Siegesbeckia pubescens herb and its chemical constituents were tested for the ability to inhibit lipopolysaccharide (LPS)-induced nitric oxide (NO) production in BV2 microglia. The methanol extract and the 90% MeOH fraction of S. pubescens effectively attenuated lipopolysaccharide-induced nitric oxide production. Several steps of chromatography yielded eight ent-kaurane diterpenes (1-8) and one ent-pimarane diterpene (9) from the 90% MeOH fraction. Among these compounds, compounds 2-9 showed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…For searching the anti-inflammatory natural products employing RAW 264.7 cells and HT-29 cells as an in vitro assay system, we further investigated S. pubescens herbs, which was previously reported that extract, fractions, its isolated diterpenes have the anti-neuroinflammatory activities. 14) Moreover, we have attempted to isolate another phtyochemicals, targeting for the treatment of IBD. This methanolic extract was then suspended in DW and successively partitioned with CH 2 Cl 2 and DW.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For searching the anti-inflammatory natural products employing RAW 264.7 cells and HT-29 cells as an in vitro assay system, we further investigated S. pubescens herbs, which was previously reported that extract, fractions, its isolated diterpenes have the anti-neuroinflammatory activities. 14) Moreover, we have attempted to isolate another phtyochemicals, targeting for the treatment of IBD. This methanolic extract was then suspended in DW and successively partitioned with CH 2 Cl 2 and DW.…”
Section: Resultsmentioning
confidence: 99%
“…11) In pharmacological studies, it was reported that S. pubescens has shown cartilage protective and analgesic activities, and an inhibitory activity on immediate hypersensitivity. [12][13][14] Also, it was reported that entkaurane and ent-pimarane diterpenenes from S. pubescens and flavonoids from S. glabrescens have the anti-inflammatory effects on the LPS-stimulated BV2 microglials. 14,16) QDE was isolated from Croton schiedeanus and showed the vasorelaxant activity with the NO/cyclic guanosine monophosphate pathway.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations